PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBANTUAN MEDIA ANIMASI INTERAKTIF BERBASIS GAME EDUKASI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Adyani, Laely; Agustini, Rudiana; Raharjo, Raharjo (Universitas Negeri Surabaya, 2015)
The aim of this research is to produce learning material and educational game that feasible to improve student?s motivation and learning achievement. The development of learning material and educational game used Four D Model and was tested in class XI of SMA Muhammadiyah 2 Sidoarjo second semester in academic year 2013/2014 with One-group Pretest-Posttest Design. The data collection used validation method, observation, test, and quetionnaires. The data analysis techniques used descriptive analysis of quantitative, qualitative, and correlative hypothesis test. The results of this research are: 1) Learning material and educational game developed has a valid category; 2) Learning material and educational game in terms of feasibility of lesson plans with good category.3) Student?s activities in accordance with the direct instruction model with the highest activities are learning by educational game, doing student activity sheet, and listening to the teacher explanation. 4) 91.67 percent of students are getting completeness and the n-gain score with high category. 5) Student?s motivation with high category. 6) The correlation of student?s learning achievement and motivation level is significant and showed a moderate positive correlation. It?s conclusion that the learning material and educational game are feasible to improve student?s motivation and learning achievement. Penelitian ini bertujuan menghasilkan perangkat pembelajaran dan media game edukasi yang layak untuk meningkatkan motivasi dan hasil belajar siswa. Pengembangan perangkat dan media game edukasi menggunakan model Four-D dan diujicobakan di kelas XI SMA Muhammadiyah 2 Sidoarjo semester genap tahun ajaran 2013/2014 dengan One-Group Pretest-Posttest Design. Pengumpulan data menggunakan metode validasi, observasi, tes, dan angket. Teknik analisis data menggunakan analisis deskriptif kuantitatif, kualitatif dan uji hipotesis korelatif. Hasil penelitian ini menunjukkan: 1) Perangkat pembelajaran dan media game edukasi yang dikembangkan berkategori valid; 2) Perangkat pembelajaran dan media game edukasi ditinjau dari keterlaksanaan RPP berkategori baik; 3) Aktivitas siswa sesuai dengan model pembelajaran langsung dengan aktivitas tertinggi yaitu: mengoperasikan game edukasi, mengerjakan LKS, dan memperhatikan penjelasan guru; 4) 91.67% siswa tuntas dalam pembelajaran dengan N-gain berkategori tinggi; 5) Motivasi siswa dalam pembelajaran berkategori baik; 6) Korelasi antara motivasi dan hasil belajar siswa adalah signifikan dengan kekuatan korelasi yang cukup kuat. Disimpulkan bahwa perangkat pembelajaran dan media game edukasi yang dikembangkan adalah layak dan dapat digunakan untuk meningkatkan motivasi dan hasil belajar siswa.